Pengembangan Penghapus Papan Tulis Putih Menggunakan Metode TRIZ - Faisal Arif Nurgesang (Faculty of Industrial Technology Universitas Islam Indonesia, 2019)
In Faculty of Industrial Technology Islamic University of Indonesia, whiteboards are used as a medium of learning in the classroom. Generally, instructors use non-permanent markers to make it easy to clean with an eraser. The problem that occurs is if this eraser is often used, the ability will decrease. This is caused by the large amount of ink markers that have been attached to the eraser cloth so that some ink that can not stick in the form of fine grains eventually falls and collects in the dirt container. These fine grains can contaminate clothes, hands, and other body parts. In addition, there are remnants of ink markers on the board that can hinder to write the next material. But to overcome this, there is a contradiction that is if an eraser is often used, the ability will decrease. To eliminate this contradiction, a systematic method of problem solving was used, namely TRIZ method. This method helps to provide solutions through the principle of preliminary action. This principle was realized by adding a spray mechanism that is used just before the erasing process is carried out. Testing the ability of the eraser was done on a whiteboard with ink markers with the size of 50 x 50 cm. The results show that the new eraser that has been developed is able to bind more ink markers and can completely erase so that it can write the next material clearly.